Day 1 Tue, August 11, 2015 2015
DOI: 10.2118/174592-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Salinity Waterflooding in Low Permeability Sandstone: Coreflood Experiments and Interpretation by Thermodynamics and Simulation

Abstract: In recent years, low salinity waterflooding (LSWF) has been a promising technique to recover oil in sandstone reservoirs. In view of research results for the last decade, it is acknowledged that substantial oil recovery beyond conventional waterflooding from sandstone is wettability alteration. However, the major contributor to wettability alteration is still uncertain. Therefore, this paper investigates this major mechanism and shows how it is involved in the process of IOR. Rock and oil surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In the past 15 years the research on low salinity water injection in relation to improved oil recovery has accelerated. In some petroleum fluids there is substantial increase from injection of low salinity brine, but in others there is no effect of salt content in the injected brine on improved oil recovery . Some authors are of the opinion that even after some 500 published papers, the mechanisms of low salinity water injection remain largely unknown .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past 15 years the research on low salinity water injection in relation to improved oil recovery has accelerated. In some petroleum fluids there is substantial increase from injection of low salinity brine, but in others there is no effect of salt content in the injected brine on improved oil recovery . Some authors are of the opinion that even after some 500 published papers, the mechanisms of low salinity water injection remain largely unknown .…”
Section: Introductionmentioning
confidence: 99%
“…In some petroleum fluids there is substantial increase from injection of low salinity brine, but in others there is no effect of salt content in the injected brine on improved oil recovery. 12 Some authors are of the opinion that even after some 500 published papers, the mechanisms of low salinity water injection remain largely unknown. 13 In all the past work, the molecular structure of the fluid−fluid interface has been neglected except in a recent paper by Alvarado et al 14 The formation of organized molecular structures at fluid− fluid interfaces increases interfacial viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Several oil companies, such as BP [34], Shell [35], Saudi Aramco [36], and PetroChina [17,18,21,37] have conducted numerous lab experiments, i.e., Log-Inject-Log, Single Well Chemical Tracer Test (SWCTT), and field scale trials. Their results have shown that, while in some cases LSWF has achieved an additional 5-25% oil recovery, in other cases, only minor incremental oil recovery was observed [38].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of smart/modified water flooding was first proposed by Morrow et al [1]; leading to further investigations with regards to the impact of injected water composition on oil recovery [2][3][4][5][6][7][8][9]. In simple words, smart/modified water flooding deals with either the addition of active ions/salts or removal of in-active ions/salts from the injection brine.…”
Section: Introductionmentioning
confidence: 99%